Manajemen Pembelajaran Berdiferensiasi dalam Perspektif POAC di Sekolah Dasar - Aniq Jihan Furoidah; Ngasbun Egar; Aryo Andri (Cetta: Jurnal Ilmu Pendidikan, 2026)
Differentiated instruction has become an important approach in accommodating the diverse characteristics of students in elementary schools; however, its success is highly influenced by effective learning management. This study aims to analyze the management of differentiated instruction from the perspective of POAC, which includes planning, organizing, actuating, and controlling. This study employed a qualitative approach with a case study design. The data sources were obtained from one principal, three teachers, three students, and one school committee member. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the management of differentiated instruction was implemented through: (1) planning by designing learning tools that accommodate students’ readiness, interests, and learning profiles; (2) organizing through role distribution and coordination among teachers and the principal; (3) actuating through the application of content, process, and product differentiation; and (4) controlling through supervision, evaluation, and reflection. However, the implementation still faces challenges, including limited teacher understanding, time constraints, and suboptimal supervision. This study contributes to the development of educational management, particularly in integrating differentiated instruction with the POAC management framework in elementary schools to improve the quality of learning.